Технология изготовления и использования псалия с поселения Поляны — I (Харьковская область) - Усачук, А. Н. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryA. Usachuk. The Technique of to Make and to Use Cheek-piece from the Settlement of Polyani–I (Kharkov Region)The article deals the famous in scientific literature cheek-piece from settlement Polyani–I in Izumski district Kharkov region. The author was made traceology analyses. This analyses allowed to determine the essential methods of prepare — cut, plane, boring, and cultivate abrasive. The trace of threadbare allowed to make conclusion that is the right cheek-piece.